First to answer
Answer:
A. The coefficients of z are the same, but the constant terms are different.
Step By step Explanation:
2(z – 1) = 4(z + 5)
Step 1: Simplify both sides of the equation.
2(z−1)=4(z+5)
(2)(z)+(2)(−1)=(4)(z)+(4)(5)(Distribute)
2z+−2=4z+20
2z−2=4z+20
Step 2: Subtract 4z from both sides.
2z−2−4z=4z+20−4z
−2z−2=20
Step 3: Add 2 to both sides.
−2z−2+2=20+2
−2z=22
Step 4: Divide both sides by -2.
−2z/−2 = 22/−2
z=−11
The coefficients for z are the same, but the constants are different.